Investigation of the Relationship Between Bone Mineral Density, Kinesiophobia, Fear of Falling, Anxiety and Depression Levels in Patients with Osteoporosis - Cansın Medin Ceylan; Merve Damla Korkmaz (Galenos Yayinevi, 2023)
Objective:To evaluate the relationship between kinesiophobia, fear of falling, anxiety, and depression levels in women with osteoporosis (OP).Materials and Methods:Female participants with OP were included in our cross-sectional observational study and their fear of falling and movement, anxiety and depression levels were questioned. Demographic data (age, body mass index, fracture history), and dual X-ray absorptiometry data were recorded. Tampa Scale of Kinesiophobia (TSK), Fall Efficacy Scale (FES), Hospital Anxiety, and Depression Scale were used.Results:Based on their history of fracture, 77 individuals were divided into two groups: OP with fracture (n=33) and OP without fracture (n=44). The findings of the bone mineral density correlated negative with the TSK, FES, and depression levels (p<0.05). FES, TSK, anxiety, and depression scores were positively correlated (r=0.232; r=0.241; r=0.296). Only the existence of the fracture and anxiety levels showed a statistical relationship in the inter-group analysis (p=0.003). No statistically significant differences were detected between the fracture history and TSK, FES, and depression scores (p>0.05).Conclusion:Fall efficacy was associated with kinesiophobia, anxiety, and depression. Therefore, care should be taken when warning OP patients to prevent negative consequences that may occur due to fracture. In addition to the negative consequences of fractures, balance and strengthening exercises and how to reduce falls should be emphasized.